Hot Rod Harry - Petrie, Catherine; Sharp, Paul (Chicago : Childrens Press, 1982)
Hot Rod Harry rides so fast on his bike he almost seems to fly like a bird or a jet.
"Level B, early fluent"--Cover p. [4].
1.4
K-3
Keywords: Bicycles and bicycling -- Fiction; Bicycles -- Fiction; Readers (Elementary).